FLUID VISCOSITY DETERMINATION IN EXPERIMENT BY OBSERVING UPWARD MOTION OF A BALL IN A CYLINDER USING DIGITAL CAMERA - NUR TAJUDDIN (NIM.20207063), MUHAMMAD
By observing motion of a ball in a cylinder filled by fluid, viscosity of the fluid can be determined. As the initial condition the ball was placed and held at the bottom of the cylinder. Then, it was released and the ball moved to surface of the fluid under influence of buoyant force (Archimedes force), gravitational force, and drag force (Stokes force). Viscosity of the fluid can be calculated from terminal velocity of the ball, which is analyzed from the film of the ball motion recorded using digital photo camera. In order to analyze the motion, the film is first transferred to a laptop and then played. A JavaScript counter program and a stopwatch are used to determine the time when the ball passed a certain position as recorded in the film. Then a plot of position versus time is drawn in order to obtain ball terminal velocity.